Art Hamburg : Internationale Messe Osteuropäischer Kunst. - Art Hamburg 1993 (Hamburg : Hamburg Messe und Congress GmbH, 1993)
Anderle, Jiri ; Pusenkoff, George ; Bartuszova, Maria ; Kolar, Jiri ; Kralik, Jroslav ; Vysusil, Karel ; Pacovska, Kveta ; Noll, Milos ; Vozniak, Jaroslav ; Hampl, Josef ; Aubrechtova, Pavla ; Frelih, Crtomir ; Podgornik, Dusan ; etc.
Art Hamburg : Internationale Messe Osteuropäischer Kunst, Hamburg, 9. - 12. Dezember 1993
boek